2021
DOI: 10.1155/2021/9920443
|View full text |Cite|
|
Sign up to set email alerts
|

[Retracted] Complexity Computer Simulation in the Study of the Overall Playing Method of Campus Football

Abstract: With the mutual exchange and integration of world football, modern football is in an increasingly comprehensive direction. This research mainly discusses complexity computer simulation in the study of the overall play of campus football. Complexity computer simulation is used to design the background of the simulated football field, and the area is divided according to the size ratio of the actual football field. Then, it uses drawing software to draw the football and player controls. The construction of the k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Figure 1 shows the functional requirements of the football tactical rehearsal model. Players who play a specific role in a tactical formation can clearly change roles through replacement, or they can dynamically change roles according to tactical needs [7]. In short, football tactical analysis can be described as the result of a complex process, which includes strategic decisions made before the game and tactical behaviors executed at different organizational levels in the process of the game [8].…”
Section: Application Of the Multiple Regressionmentioning
confidence: 99%
“…Figure 1 shows the functional requirements of the football tactical rehearsal model. Players who play a specific role in a tactical formation can clearly change roles through replacement, or they can dynamically change roles according to tactical needs [7]. In short, football tactical analysis can be described as the result of a complex process, which includes strategic decisions made before the game and tactical behaviors executed at different organizational levels in the process of the game [8].…”
Section: Application Of the Multiple Regressionmentioning
confidence: 99%
“…Zhao used complexity computer simulation to simulate a football field, combined with mapping software to draw the football and players to develop real-time tactics, and the experimental results showed that using complexity computer simulation for early school football overall play with high accuracy of passing and running, which can provide implications for the overall tactics of football [13].…”
Section: Introductionmentioning
confidence: 99%